(untitled) (The Pakistan Development Review, 2011)
Using social opportunity function approach, this work assesses, firstly, the change in and access to education and employment opportunities available to the population and secondly, how equitably these opportunities are distributed. Opportunity Index (OI) and Equity Index of Opportunities (EIO) are calculated to measure and quantify the extent of progress made in these two most important socio-economic components of development. Based on data, extracted from Pakistan Social and Living Standards Measurement (PSLM) Surveys of 1998-99 and 2007-08, the present work finds that growth process has resulted in increased inequalities both in education and employment opportunities over the study period. Average opportunities available to population increased for education while a decline in average employment opportunities is documented in 2007-08 as compared to 1998-99. OI registered an increase for primary and secondary levels of education. EIO improved at primary level, remained stagnant for secondary level and decreased for literacy rate over the time. Moreover, EIO for employment opportunities, suggesting equitable distribution for employment and paid employment, registered a decrease and opportunities distribution turn inequitable when calculated based on average monthly income earned. Findings of the paper suggest that policies should be focused to actively engage the marginalised groups of the society in growth process through improvement in higher education and more equitable distribution of opportunities. JEL classification: C46, D63, E24, I24, O12 Keywords: Inclusive Growth, Inequality, Opportunity Curve, Opportunity Index, Equity Index of Opportunities, Pakistan